2018
DOI: 10.3389/fphar.2018.01445
|View full text |Cite
|
Sign up to set email alerts
|

Danshensu for Myocardial Ischemic Injury: Preclinical Evidence and Novel Methodology of Quality Assessment Tool

Abstract: Background: Danshensu (DSS) possesses unique bioactivity on the cardiovascular system. However, there is a lack of systematical summary of DSS for acute myocardial ischemia injury and no quality assessment tool for the systematical review of cell experiments. Here, we aimed to assess the preclinical evidences and possible mechanisms of DSS for myocardial ischemia injury, and to develop a quality assessment tool for the systematical review of cell experiments.Methods: Thirty-two studies with 473 animals and 134… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…According to CAMARADES 10-item checklist, the score of the included studies was medium. They are similar to other animal studies, and the main limitations were that no study reported sample size calculation, allocation concealment, and blinding of outcome assessment (Bao et al, 2018). Inadequate sample size could not reach the approximately threshold with sufficient power and efficacy (Bacchetti 2010).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…According to CAMARADES 10-item checklist, the score of the included studies was medium. They are similar to other animal studies, and the main limitations were that no study reported sample size calculation, allocation concealment, and blinding of outcome assessment (Bao et al, 2018). Inadequate sample size could not reach the approximately threshold with sufficient power and efficacy (Bacchetti 2010).…”
Section: Discussionmentioning
confidence: 60%
“…The modified item is the use of anesthetic with no intrinsic organ-protective activity. Our newly developed scale specially designed for cell studies was used for the assessment of risk of bias in cell experiments (Bao et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis and autophagy are two pivotal events of programmed cell death in the pathological mechanisms of AMI injury (Bao et al, 2018). Cardiomyocyte apoptosis and autophagy occur during sustained and severe ischemia, usually involving myocardial pump failure (Guo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some checklists have been developed to evaluate the quality of in vivo animal intervention experiments (Hooijmans et al, 2014; Zhang et al, 2017), including the SYstematic Review Centre for Laboratory animal Experimentation (SYRCLE)'s RoB tool and the Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies (CAMARADES) 10-item checklist. About in vitro studies, the ROB assessment can refer to 10-item scale developed by our group (Bao et al, 2018). However, there are no quality assessment tools for a systematical review of ex vivo studies.…”
Section: Discussionmentioning
confidence: 99%